ANALISIS SARANA PRASARANA TAMAN KANAK-KANAK DI KECAMATAN TAMPAN KOTA PEKANBARU - Maria Olfa; Wusono Indarto; Devi Risma (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The research belongs to the descriptive research. The purpose this research was to know how the kindergartens’ school facilities at Tampan district, Pekanbaru. The population of this research was 48 kindergartens’ at Tampan district and the sample was 43 kindergartens’ by using 5% Error percentages. The data were collected by using observation technique in the forms of interview and documentation. The data were analyzed by using descriptive analysis with percentages. The result showed that the kindergartens’ school facilities at Tampan district, Pekanbaru belong to enough category with percentage 60.15% with: The school facilities were wide of schools’ land with percentage 72.86% belong good category, building or classrooms with percentage 69.18% belong to good category, and schools furniture with percentage 71.88% belong to good category too, the teaching aids whether indoor or outdoor with each of percentages was 49.11% and 55.81% belong to the enough category.Key:School facilities